Intraguild predation between the aphidophagous ladybird beetles Harmonia axyridis and Coccinella undecimpunctata (Coleoptera: Coccinellidae): the role of body weight - Sandra FÉLIX; António Onofre SOARES (European Journal of Entomology, 2004)
The magnitude, direction and symmetry of intraguild predation (IGP) between the developmental stages of the aphidophagous Harmonia axyridis Pallas and Coccinella undecimpunctata L. were characterized and compared. Mobility and body weight were the main factors affecting the magnitude of IGP.H. axyridis was more often the predator than C. undecimpunctata and eggs the most vulnerable developmental stage. There was significant asymmetrical IGP on eggs by the second and later, and fourth larval stages of H. axyridis and C. undecimpunctata, respectively. Asymmetrical IGP of pupae was only recorded for the fourth larval stage of H. axyridis. There was no IGP between adults, but larvae of both species attacked heterospecifics. The best model of the relationship between rate of predation and the difference in the body weight of IG predator and prey differs for the two ladybirds. A small difference in the body weights leads to a marked increase in the rate of predation in H. axyridis but not in C. undecimpunctata. In asymmetrical combinations, increase in body weight of the intraguild predator did not significantly increase the rate of predation. Mobility and body weight were not the only important parameters involved in the symmetry of IGP. Aggressive behaviour of H. axyridis negatively affected the survival of C. undecimpunctata.